Head movements affect skill acquisition for ball trapping in blind football. - Takumi Mieda; Masahiro Kokubu (PLoS ONE)
Blind football players use head movements to accurately identify sound location when trapping a ball. Accurate sound localization is likely important for motor learning of ball trapping in blind football. However, whether head movements affect the acquisition of ball-trapping skills remains unclear. Therefore, this study examined the effect of head movements on skill acquisition during ball trapping. Overall, 20 sighted male college students were recruited and assigned to one of the following two groups: the conventional training group, where they were instructed to move leftward and rightward to align their body with the ball's trajectory, and the head-movement-focused group, where they were instructed to follow the ball with their faces until the ball touched their feet, in addition to the conventional training instructions. Both groups underwent a 2-day training for ball trapping according to the specific instructions. The head-movement-focused group showed a decrease in errors in ball trapping at near distances and with larger downward head rotations in the sagittal plane compared to the conventional training group, indicating that during the skill acquisition training for ball trapping, the sound source can be localized more accurately using larger head rotations toward the ball. These results may help beginner-level players acquire better precision in their movements while playing blind football.